STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MEWUJUDKAN PEMBELAJARAN EFEKTIF DI TAMAN KANAK-KANAK - Andriani Chondro Retno; Sartini; Desilva Sindra Javanis; Darsinah; Wafroturrohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe various leadership strategies implemented by the principal of TK Kemala Bhayangkari 67 Sragen in achieving effective learning. The study employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. Data validity is ensured through data source triangulation. The results indicate that TK Kemala Bhayangkari 67 Sragen has shown a high commitment to enhancing educational quality by implementing effective leadership strategies. The principal plays a significant role in fostering synergy among the foundation, teachers, and parents to create an excellent learning environment. These strategies include regular supervision and evaluation, distributing leadership to coordinators with specific experience and expertise, and actively involving parents in decision-making. Periodic evaluation and leadership rotation have proven effective in improving communication, cooperation, and overall school performance to achieve effective learning.